Characterization of Transcription Regulatory Domains of OsMADS29: Identification of Proximal Auxin-Responsive Domains and a Strong Distal Negative Element - Khurana, Ridhi; Bhimrajka, Sanchi; Sivakrishna Rao, Gundra; Verma, Vibha; Boora, Neelima; Gawande, Gautam; Kapoor, Meenu; Rao, Khareedu Venkateswara; Kapoor, Sanjay (Frontiers in Plant Science, 2022)
OsMADS29 (M29) is a seed-specific MADS-box transcription factor involved in programmed cell death of nucellar tissue and maintaining auxin:cytokinin homeostasis. It affects embryo and endosperm development and starch filling during seed development in rice. Its expression seems to be tightly regulated by developmental, spatial, and temporal cues; however, cis- and trans-regulatory factors that affect its expression are largely unknown. In silico analysis of the 1.7 kb upstream regulatory region (URR) consisting of 1290 bp promoter and 425 bp 5’-UTR regions revealed several auxin-responsive and seed-specific cis-regulatory elements distributed across the URR. In this paper, the analysis of four URR deletions fused to a downstream β-glucuronidase (GUS) reporter in transgenic rice has revealed the presence of several proximal positive elements and a strong distal negative element (NE). The promoter regions containing auxin-responsive elements responded positively to the exogenous application of auxins to transgenic seedlings. The proximal positive elements are capable of driving reporter expression in both vegetative and reproductive tissues. The NE, on the other hand, strongly suppresses the reporter gene expression in both vegetative or reproductive tissues. In a transient onion peel assay system, the NE could reduce the efficacy of 2x CaMV 35S promoter by ~90%. Our results indicate the existence of a complex array of positive and negative regulatory regions along with auxin-responsive elements guiding the development-dependent and spatial expression of M29.